Housing and the politics of Nationally Strategic Infrastructure Planning in England. (January 2023) - Hickman, Hannah; While, Aidan
Abstract: The 2008 Planning Act introduced a new approach for determining large ('nationally significant') infrastructure projects in a new national process that would unify consent regimes and speed up decisions within fixed timescales outside of local planning. Major housing schemes have been excluded from this process, despite repeated attempts by recent UK governments to allocate more land for housebuilding through parallel reforms to the English planning system. This paper explores why Nationally Significant Infrastructure Planning (NSIP) has not been used for housing schemes, using the example of housing to reflect on debates about potential democratic deficits in the NSIP process and the selective politicisation of infrastructure planning in England. In doing so, the paper makes a distinctive contribution to practice and research by linking together debates about the politics of planning for housing in England and international literature on democratic process in the delivery of critical infrastructure. Highlights: The Nationally Significant Infrastructure Planning (NSIP) regime in England currently excludes housing. NSIP has the potential to make a contribution to addressing the housing delivery challenge in England. Interest in the NSIPs for housing reflects the absence of a strategic approach to housing planning and delivery. Bringing housing into the regime would be politically challenging because of the perceived democratic deficit of the NSIP regime. This reveals wider insights into how infrastructure planning is insulated from prevailing democratic process, often linked to pro-development state strategies.